2021
DOI: 10.2147/cmar.s305108
|View full text |Cite
|
Sign up to set email alerts
|

The Long Noncoding RNA MAGI1-IT1 Regulates the miR-302d-3p/IGF1 Axis to Control Gastric Cancer Cell Proliferation

Abstract: Background: MAGI1-IT1 is a long non-coding RNA (lncRNA) previously reported to regulate several cancer types, but its functional role in gastric cancer (GC) remains to be defined. This study therefore explored the mechanistic role played by MAGI1-IT1 in the regulation of GC cell proliferation. Methods: 120 pairs of GC patient tumor, paracancerous tissues, human GES-1 control cells and human AGS, MKN-74, MKN-45, and MGC-803 GC cell lines were used to detected MAGI1-IT1, miR-302d-3p, and IGF1 expression by a qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Ning et al found that DSCAM-AS1 can accelerate cell value-addition and migration in osteosarcoma through GPRC5A signaling ( Ning and Bai, 2021 ). Wang et al found that MAGI1-IT1 has a regulatory role in controlling the value-addition of gastric cancer ( Wang et al, 2021 ). Sun et al found that LINC01133 also has a regulatory effect on the value-added of gastric cancer ( Sun et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ning et al found that DSCAM-AS1 can accelerate cell value-addition and migration in osteosarcoma through GPRC5A signaling ( Ning and Bai, 2021 ). Wang et al found that MAGI1-IT1 has a regulatory role in controlling the value-addition of gastric cancer ( Wang et al, 2021 ). Sun et al found that LINC01133 also has a regulatory effect on the value-added of gastric cancer ( Sun et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-144-3p is associated with the progression of several cancers, inhibiting cervical cancer [104], gastric cancer [105], and non-small-cell lung cancer (NSCLC) [106] in terms of proliferation, invasion, and migration. The other three miRNAs are associated with promoting tumor proliferation [107], migration [108], and drug resistance [109]. The downregulation of their expression after radiotherapy may play a role in blocking tumor invasion.…”
Section: Exosomal Mirnas 411 Brain Metastasesmentioning
confidence: 99%
“…Mechanistically, MAGI1-IT1 sequesters miR-302d-3p enabling accumulation of its target insulin-like growth factor 1 (IGF1). Knock-down of the lncRNA in the human gastric cancer AGS and MGC-803 cell lines decreases proliferation in vitro and tumor growth in nude mice [ 207 ].…”
Section: Magi Cernas In Carcinogenesismentioning
confidence: 99%